2018
DOI: 10.20411/pai.v3i1.235
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Associated with Death After Initiating Treatment for Tuberculosis and HIV in Patients with Very Low CD4 Cells

Abstract: BackgroundThe risk of short-term death for treatment naive patients dually infected with Mycobacterium tuberculosis and HIV may be reduced by early anti-retroviral therapy. Of those dying, mechanisms responsible for fatal outcomes are unclear. We hypothesized that greater malnutrition and/or inflammation when initiating treatment are associated with an increased risk for death.MethodsWe utilized a retrospective case-cohort design among participants of the ACTG A5221 study who had baseline CD4 < 50 cells/mm3. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
2
13
0
1
Order By: Relevance
“…During the last decade, TB has been highly prevalent among HIV/AIDS patients who died [ 5 , 10 , 11 , 18 ]. Additionally, we found weight loss associated to death through the univariate analysis, in agreement with early mortality in TB-HIV coinfected patients presenting malnutrition or low body mass index [ 19 , 20 ]. It is worth mentioning that weight loss and gastrointestinal disorders can be correlated variables [ 20 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…During the last decade, TB has been highly prevalent among HIV/AIDS patients who died [ 5 , 10 , 11 , 18 ]. Additionally, we found weight loss associated to death through the univariate analysis, in agreement with early mortality in TB-HIV coinfected patients presenting malnutrition or low body mass index [ 19 , 20 ]. It is worth mentioning that weight loss and gastrointestinal disorders can be correlated variables [ 20 ].…”
Section: Discussionsupporting
confidence: 71%
“…It is worth mentioning that weight loss and gastrointestinal disorders can be correlated variables [ 20 ]. Our multivariate analysis corroborated greater risk of death among those TB-HIV coinfected patients, similar with those coming from low-income regions, whose poverty, schooling, and social vulnerability index decrease the odds of access ART [ 6 , 19 , 21 26 ]. We observed an augmented risk of death among those patients presenting gastrointestinal disorders, especially oropharyngeal–esophageal candidiasis, which is recognized as an indicator of advanced immunosuppression [ 27 ].…”
Section: Discussionsupporting
confidence: 71%
“…Immune activation at baseline [11,49] and failure to resolve or increased immune activation after ART initiation have been described as risk factors for mortality in HIV-associated tuberculosis cohorts [12, 13, 50]. One of these studies was an outpatient cohort study that followed participants with HIV-associated tuberculosis and showed that higher pre-ART levels of MCP-1/CCL2, eotaxin, IL-10, TNF-α, and IL-6 were associated with 6-month mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying causes of mortality remain poorly characterized. In outpatient cohorts with HIV-associated tuberculosis, early mortality has been associated with high baseline immune activation [11,12], persistent or increased immune activation on antiretroviral therapy (ART) [12], and failure to recover cellular immune responses to Mycobacterium tuberculosis [13]. In Africa, disseminated tuberculosis is found in 88% of autopsies of patients dying with HIV-associated tuberculosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, no difference was observed in sCD14, IL-8 and Th1/Th2/Th17 cytokines between patients who died or were discharged. Biomarker concentrations are observable outcomes of complex biological processes that are only partially understood, and this may be the reason for a lack of consensus regarding immunological markers in prediction of mortality in HIV/AIDS patients [30][31][32][33][34] . Curiously, we observed much higher levels of in ammatory biomarkers sCD14, IL-8, and IL-6 than for other cytokines, which is consistent with the in ammatory status of the HIV/AIDS patients 35 .…”
Section: Discussionmentioning
confidence: 99%